DAMPAK PERUBAHAN BUDAYA BUTON SELATAN PADA PEMBELAJARAN SEKOLAH DASAR - Sarnia; Sitti Nurqalbiyah Moebbrey; Asniawati; Nabil Khaufman; Haliadi (CV. Adiba Aisha Amira, 2026)
This research investigates the significant impact of cultural transformation in South Buton Regency on the learning dynamics of elementary school students. As a region deeply rooted in maritime heritage and traditional Sultanate values, South Buton currently faces a cultural shift due to rapid modernization and digital globalization. The primary problem addressed is the erosion of local ethics and social characters among the younger generation, which directly influences pedagogical outcomes in formal education. Using a qualitative descriptive method with a field study approach, data were gathered through comprehensive observations and interviews with educators and local community leaders. The results reveal that while students demonstrate improved proficiency in digital literacy and technology use, there is a marked decline in the practice of traditional character-based interactions and local wisdom. The study concludes that integrating local values into the school curriculum is essential to maintain cultural identity while embracing modern education.